Faculty and Course Development for Online Degree Programs - Way, Raleigh; Lloyd, David; Champion, Deborah (Valdosta State University, 2011)
The Center for Online Learning (COL) at Georgia Southern University (GSU) develops courses for online degree programs. The process includes two weeks of online training for faculty who teach the courses. The two‐week online training course provides an online course experience for faculty from a student’s perspective. Faculty must complete 4 learning modules. Each module has a specific pedagogical focus that asks faculty to think through the teaching and learning experience. In the first module, faculty examine their current teaching practice and reflect on how they might teach a particular subject online. The second module explores the concept of instructional alignment; Bloom’s Taxonomy is used as the vehicle for the discussion. The third module asks the faculty to consider how they engage students in dialogue in an online course; here we explore discussion guidelines and rubrics. In the fourth module, faculty are asked to design on paper a unit of instruction for an online class. The process that GSU uses for faculty and course development will be outlined. Emphasis will be placed on best practice concepts for online course design and the pedagogical aspects of faculty development.
Presented at the Online Lifeline Conference, Valdosta State University, Valdosta, Georgia, February 16-18, 2011.
Keywords: Distance education; Curriculum planning--United States